The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.2147/jir.s399480
|View full text |Cite
|
Sign up to set email alerts
|

TMAO Promotes NLRP3 Inflammasome Activation of Microglia Aggravating Neurological Injury in Ischemic Stroke Through FTO/IGF2BP2

Pengxin Ge,
Huijie Duan,
Chunrong Tao
et al.

Abstract: Stroke is a kind of cerebrovascular disease with high mortality. TMAO has been shown to aggravate stroke outcomes, but its mechanism remains unclear. Materials and Methods: Mice were fed with 0.12% TMAO for 16 weeks. Then, mice were made into MCAO/R models. Neurological score, infarct volume, neuronal damage and markers associated with inflammation were assessed. Since microglia played a crucial role in ischemic stroke, microglia of MCAO/R mice were isolated for high-throughput sequencing to identify the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Studies have found that YTHDF1 could enhance the translation of NLRP3 and promote inflammatory responses [ 25 ]. Furthermore, IGF2BP2 negatively feedback regulated the activation of the NLRP3 inflammasome in microglia [ 26 ]. However, the underlying mechanism of m 6 A modification in Hcy-induced cognitive impairment has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that YTHDF1 could enhance the translation of NLRP3 and promote inflammatory responses [ 25 ]. Furthermore, IGF2BP2 negatively feedback regulated the activation of the NLRP3 inflammasome in microglia [ 26 ]. However, the underlying mechanism of m 6 A modification in Hcy-induced cognitive impairment has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In order to detect the mRNA expression levels of related inflammatory factors, RT-qPCR was performed according to the description [ 32 ]. The following primers were used: β-actin: forward TGAGCTGCGTTTTACACCCT, reverse GCCTTCACCGTTCCAGTTTT; IL-1β: forward CACCTCTCAAGCAGAGCACAG, reverse GGGTTGCATGGTGAAGTCAAC; IL-6: forward GCTACCAAACTGGATATAATCAGGA, reverse CCAGGTAGCTATGGTACTCCAGAA; TNF-α: forward GACCCTCACACTCAGATCATCTTCT, reverse CCTCCACTTGGTGGTTTGCT.…”
Section: Methodsmentioning
confidence: 99%
“…In order to detect the mRNA expression levels of related inflammatory factors, RT-qPCR was performed according to the description [32]. The following primers were used: β-actin: forward TGAGCTGCGTTTTACACCCT, reverse GCCTTCACCGTTCCAGTTTT; IL-1β: forward CACCTCTCAAGCAGAGCACAG, reverse GGGTTGCATGGTGAAGT-CAAC; IL-6: forward GCTACCAAACTGGATATAATCAGGA, reverse CCAGGTAGC-TATGGTACTCCAGAA; TNF-α: forward GACCCTCACACTCAGATCATCTTCT, reverse CCTCCACTTGGTGGTTTGCT.…”
Section: Real-time Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%